Bilateral Symmetric Retinal Pigmentation Versus Heterochromia: A Case of Waardenburg Syndrome - Elahe Heidari, Gholamhossein Yaghoobi (Pakistan Journal of Ophthalmology, 2018)
This report describes a 22 year intellectual female who presented with poor vision while working on a microscope. Slit lamp biomicroscopic examination showed heterochromia iridis and retinal pigmentary changes that disclosed Waardenburg Syndrome (WS) type 2. Except of white forelock, we could not find any other association or anomaly elsewhere. Ophthalmological examination revealed WS type 2 with heterochromia iridis. She also had the specific pattern of bilateral posterior heavy retinal pigmentation versus peripherally albinotic pattern. This retinal finding in WS type 2 is the first report in literature to the best of our knowledge.